1995
DOI: 10.1002/ana.410370405
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against GM1 ganglioside affect K+ and NA+ currents in isolated rat myelinated nerve fibers

Abstract: High titers of anti-GM1 ganglioside antibodies (anti-GM1 antibodies) may be implicated in lower motor neuron disease. We studied the pathogenic role of anti-GM1 antibody using the petroleum jelly-gap voltage clamp technique on isolated single myelinated rat nerve fibers. Anti-GM1 antisera were obtained from rabbits immunized with GM1 ganglioside. Extracellularly applied anti-GM1 antisera without complement activity increased both the rate of rise and the amplitude of the K+ current elicited by step depolarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
94
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(102 citation statements)
references
References 32 publications
5
94
0
3
Order By: Relevance
“…GM1 antibodies (56). A similar effect of antidiasolysyl antibodies might be responsible for the changes in neuronal excitability described here.…”
Section: Discussionsupporting
confidence: 65%
“…GM1 antibodies (56). A similar effect of antidiasolysyl antibodies might be responsible for the changes in neuronal excitability described here.…”
Section: Discussionsupporting
confidence: 65%
“…Experimental results of the effect of anti-GM1 antibodies on Na v channel function are conflicting. Anti-GM1 antibodies suppressed Na ϩ currents on isolated single myelinated rat nerve fibers in the presence of complement (Takigawa et al, 1995), although this was not confirmed by other investigators (Hirota et al, 1997). New experimental approaches are required to elucidate the contribution of antiganglioside antibody-mediated Na v channel dysfunction in the pathophysiology of AMAN.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, it is very likely that anti-GMl antibody per se caused specific effects on the action potential and ionic currents. The effect of anti-GMl antisera obtained from rabbits immunized with GM1ganglioside on single myelinated rat nerve fibers has been reported (6). High concentrations of anti-GMl antibodies with active complement induced a-marked decrease of Na+ current and caused a progressive increase of nonspecific leakage current.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that high titers of anti-GM l antisera from rabbits immunized with GM1ganglioside induce impairment of action potential with an accompanying decrease in Na+currents and an increase in K+currents in rat myelinated nerve fibers (6). However, there have been controversial results on the effect of anti-GMl antibody on nerve fibers and neurons (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%